Trauma-Disclosure, Meaning-Making, and Help-Seeking in Mothers Experiencing Homelessness: Results From a Trauma-Focused, Clinical Ethnographic Narrative Intervention - Gultekin, Laura (Violence against women, 2024)
Mothers experiencing homelessness are seldom asked about past trauma that may be causal to housing instability and poor health. There are also few validated trauma-focused interventions in family shelters. To address this gap, we tested the feasibility and acceptability of the trauma-focused clinical ethnographic narrative intervention (CENI-TF) in increasing mothers’ trauma disclosure, appraisal of its meaning in their lives, and help-seeking behaviors. We also present the qualitative findings to contextualize the intervention. Findings are organized under three major domains and nine subthemes that capture participants’ voices and experiences. The CENI-TF has the potential to promote help-seeking behaviors and interrupt recurring cycles of trauma and housing instability in this at-risk population.